Are motivational and self-regulation factors associated with 12 months’ weight regain prevention in the NoHoW study? An analysis of European adults - Palmeira, AL (2023)
Funding Information: The NoHoW study has received funding from the European Union’s Horizon 2020 Research and Innovation Programme (grant agreement number 643309). Funding Information: The NoHoW trial is a three-centre (University of Leeds (UK), The Parker Institute (Denmark) and University of Lisbon (Portugal)) 2 × 2 factorial, randomized, single-blind, controlled trial testing the proof-of-concept of a digital toolkit for weight regain prevention in over 1600 participants (European Union’s Horizon 2020 research and innovation program under grant agreement No. 643309). Publisher Copyright: © 2023, The Author(s).